2014
DOI: 10.1038/bjc.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin mesilate suppresses experimental metastasis of breast cancer cells by reversing phenotype from epithelial–mesenchymal transition (EMT) to mesenchymal–epithelial transition (MET) states

Abstract: Background:Eribulin mesilate (eribulin), a non-taxane microtubule dynamics inhibitor, has shown trends towards greater overall survival (OS) compared with progression-free survival in late-stage metastatic breast cancer patients in the clinic. This finding suggests that eribulin may have additional, previously unrecognised antitumour mechanisms beyond its established antimitotic activity. To investigate this possibility, eribulin's effects on the balance between epithelial–mesenchymal transition (EMT) and mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
344
5
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(362 citation statements)
references
References 30 publications
(40 reference statements)
9
344
5
4
Order By: Relevance
“…The survival benefit of eribulin was also apparent in patients with human epidermal growth factor receptor 2 (HER2)-negative or triple-negative breast cancer (15). Interestingly, in a preclinical study, eribulin demonstrated unique effects such as reversed EMT and induced mesenchymal-epithelial transition (MET) (16). This process may explain the clinical observation of prolonged OS in eribulin-treated patients.…”
mentioning
confidence: 99%
“…The survival benefit of eribulin was also apparent in patients with human epidermal growth factor receptor 2 (HER2)-negative or triple-negative breast cancer (15). Interestingly, in a preclinical study, eribulin demonstrated unique effects such as reversed EMT and induced mesenchymal-epithelial transition (MET) (16). This process may explain the clinical observation of prolonged OS in eribulin-treated patients.…”
mentioning
confidence: 99%
“…Among these novel therapeutic armamentariums of soft tissue sarcoma, only eribulin showed the improvement of overall survival in a phase III trial, 3 although angiosarcoma was not included in it. In addition to its antitubulin effect, unique effects of eribulin have been reported on breast cancer in vitro, such as switching the phenotype of cancer cells from mesenchymal to epithelial state, decreasing the capacity of migration and invasion of cancer cells, 4 and improving perfusion in the tumor by vascular remodeling.…”
Section: Case Of Angiosarcoma Of the Scalp Successfully Controlled Bymentioning
confidence: 99%
“…These findings are very rare, because there has been only one report of clear cell sarcoma with intraepidermal nests. 4 It still remains a possibility that nests of tumor cells bordered the epidermis mimicking intraepidermal nests. …”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that the epithelial-mesenchymal transition (EMT) is a crucial process that is often activated during cancer invasion and metastasis and also induces chemoresistance in cancer treatment (17,18). It has been reported that eribulin mesylate has significant effects on EMT-related pathways, resulting in increased antitumor effects (19,20). The present study clearly shows that eribulin mesylate has antitumor effects, namely reducing cell viability and inducing morphological changes in tumor cells, which could be beneficial in clinical therapy for gemcitabine-refractory advanced pancreatic cancer.…”
Section: Figure 2 Cell Viability In the Aspc-1 (A) And Panc-1 (B) Pamentioning
confidence: 99%